Singapore 2065 : leading insights on economy and environment from 50 Singapore icons and beyond - Quah, Euston (Singapore : World Scientific, 2016)
'This book is a collection of key insights from 50 iconic individuals of Singapore and beyond, and contains reasoned arguments, speculations and visionary expectations of Singapore's future in 50 years' time. The book discusses the distant future of Singapore's economy and the environment. What will Singapore's economic and environment landscape be like 50 years from now? Are there trends or scenarios common to the various discussions contained in this book? If there are, how big would be the impact of some of these trends? What and how should the government respond to these projections, expectations and informed visions of tomorrow? In sum, what would Singapore's economy and environment be like in 2065? The book explores a range of possible answers to these questions and more'--
Includes bibliographical references.
Keywords: Economic forecasting -- Singapore; Singapore -- Economic conditions -- 21st century; Singapore -- Environmental conditions -- Forecasting